Conservation units in the core area of the Cerrado domain: an overview on the small nonvolant mammals (Rodentia and Didelphimorphia) - Cibele R. Bonvicino; Ana Lazar; Margaret M.O. Corrêa; Marcelo Weksler; Alberto da Costa Paula; Alexandra M.R. Bezerra (Heringeriana, 2015)
A review of small non-volant mammal species of the APA Gama e Cabeça de Veado was carried out, including new surveys in the "Estação Ecológica do Jardim Botânico" (EEJBB) and "Reserva Ecológica do Instituto Brasileiro de Geografia e Estatística" (REIBGE). Thirty-one small mammal's species are registered for the APA Gama and Cabeça de Veado, including one exotic species. Didelphis albiventris, Hylaeamys megacephalus, and Oxymycterus delator were collected for the first time in EEJBB. The APA Gama-Cabeça de Veado has a central position in the Cerrado domain sharing six species with the Amazon domain, five with Atlantic Forest, and 13 with Caatinga. The APA Gama-Cabeça de Veado encompasses the home range of at least six non-volant small mammal species endemic of Cerrado domain, and it has an important role in the protection of these endemic species and species that occurs in those four South America morphoclimatic domains.